Hugh-Stovin syndrome: the 'incomplete Behcet's disease'. A case study of a young adult with recurrent pulmonary embolism and pulmonary arterial aneurysms. Issue 4 (4th July 2021) - Ukemenam, Chinedu; Muppaneni, Sivaram Prabhuji; De, Debapriya; Lacasse, Alexandre
ABSTRACT: Hugh-Stovin Syndrome (HSS) is characterized by recurrent thrombophlebitis and multiple pulmonary and/or bronchial artery aneurysms indistinguishable from the cardiovascular features seen in Behcet's disease (BD). Our case describes a 30-year-old male with recurrent pulmonary embolism and bilateral pulmonary aneurysms. Autoimmune, hypercoagulable, and infectious work up were negative. Elevated inflammatory markers and absence of the typical clinical findings seen in BD led to the diagnosis of Hugh-Stovin syndrome (HSS). Immunosuppression using steroids and azathioprine led to clinical response. Anticoagulation was continued based on risk/benefit ratio.